Bone Marrow Mesenchymal Stem Cells' Secretome Exerts Neuroprotective Effects in a Parkinson's Disease Rat Model - Mendes-Pinheiro, Bárbara; Anjo, Sandra I.; Manadas, Bruno; Da Silva, Jorge D.; Marote, Ana; Behie, Leo A.; Teixeira, Fábio G.; Salgado, António J. (Frontiers in Bioengineering and Biotechnology, 2019)
Parkinson’s disease (PD) is characterized by a selective loss of dopamine (DA) neurons in the human midbrain causing motor dysfunctions. The exact mechanism behind dopaminergic cell death is still not completely understood and, so far, no cure or neuroprotective treatment for PD is available. Recent studies have brought attention to the wide array of bioactive molecules produced by mesenchymal stem cells (MSCs), generally referred to as the secretome. Herein, we evaluated whether human MSCs-bone marrow derived (hBMSCs) secretome would be beneficial in a PD pre-clinical model, when compared directly with cell transplantation of hBMSCs alone. We used a 6-hydroxydpomanie (6-OHDA) rat PD model, and motor behavior was evaluated at different time points after treatments (1, 4 and 7 weeks). The impact of the treatments in the recovery of DA neurons was estimated by determining TH-positive neuronal densities in the substantia nigra and fibers in the striatum, respectively, at the end of the behavioral characterization. Furthermore, we determined the effect of the hBMSCs secretome on the neuronal survival of human neural progenitors in vitro, and characterized the secretome through proteomic-based approaches. This work demonstrates that the injection of hBMSCs secretome potentiated the histological recovery of DA neurons, when compared to transplantation of hBMSCs themselves, a fact that probably explains the improved behavioral performance of secretome-injected animals in the staircase test. Moreover, we observed that hBMSCs secretome induces higher levels of in vitro neuronal differentiation. Finally, the proteomic analysis revealed that hBMSCs secrete a variety of important exosome-related molecules such as those related with the ubiquitin-proteasome and histone systems. Overall, this work provided important insights on the potential use of hBMSCs secretome as a therapeutic tool for PD, and further confirms the importance of the secreted molecules rather than the transplantation of hBMSCs for the observed positive effects. These could be likely through normalization of defective processes in PD, namely proteostasis or altered gene transcription, which lately can lead to neuroprotective effects.